Impact of Multiple Types of Childhood Trauma Exposure on Risk of Psychiatric Comorbidity Among Alcoholic Inpatients - Huang, Ming-Chyi; Schwandt, Melanie L.; Ramchandani, Vijay A.; George, David T.; Heilig, Markus (Alcoholism, clinical and experimental research, 2012)
Background This study examined the prevalence of single‐ and multiple‐type childhood trauma exposure (CTE) among alcoholic patients undergoing inpatient detoxification and treatment. The relationships between various types of CTE and lifetime psychiatric comorbidities and suicide attempts were also explored. Methods A total of 196 alcoholic inpatients were assessed by Structured Clinical Interview for DSM‐IV Axis I Disorders and Childhood Trauma Questionnaire (CTQ) for CTE history. Results The overall prevalence of CTE in the entire sample was high (55.1%). Specifically, the prevalence of emotional abuse was 21.4%, physical abuse 31.1%, sexual abuse 24.0%, emotional neglect 20.4%, and physical neglect 19.9%. Regarding multiple types of CTE, 31.7 and 18.9% reported at least 2 and at least 3 CTE types, respectively. Strikingly, among those with at least 1 positive CTQ category, more than half reported 2 or more CTE types. A history of emotional abuse increased the risk of mood disorder, in particular major depressive disorder, as well as posttraumatic stress disorder (PTSD). Physical abuse contributed to the prediction of suicide attempts, while sexual abuse was associated with a diagnosis of anxiety disorder, PTSD, and multiple comobidities (e.g., anxiety and mood disorder). The number of reported CTE types or the total score of the CTQ predicted an increased risk of having single or multiple psychiatric comorbidities as well as suicide attempts. Conclusions We observed high rates of a broad range of CTE types and a trend for CTE‐specific enhancement of risk for various psychiatric outcomes among alcoholic inpatients. Of note, a dose–response relationship between number of CTE types and risk of psychiatric comorbidities as well as suicide attempts was found. We suggest a wide range of CTE should be included when exploring the effects of CTE or developing prevention and treatment strategies among alcoholic subjects.